Schelling's spatial proximity model of segregation revisited - Romans Pancs; Nicolaas J. Vriend (Queen Mary University of London, Department of Economics, 2003)
Schelling [1969, 1971a, 1971b, 1978] presented a microeconomic model showing how an integrated city could unravel to a rather segregated city, notwithstanding relatively mild assumptions concerning the individual agents' preferences, i.e., no agent preferring the resulting segregation. We examine the robustness of Schelling's model, focusing in particular on its driving force: the individual preferences. We show that even if all individual agents have a strict preference for perfect integration, best-response dynamics will lead to segregation. What is more, we argue that the one-dimensional and two-dimensional versions of Schelling's spatial proximity model are in fact two qualitatively very different models of segregation.
Keywords: C72; C73; D62; 330; Neighborhood segregation; Myopic Nash Equilibria; Best-response dynamics; Markov chain; Limit-behavior; Wohnstandort; Pr\~AƒÂferenztheorie; Markovscher Prozess; Segregation